Usefulness of magnetic resonance enterography in detecting signs of sacroiliitis in young patients with inflammatory bowel disease - Teresa Giani; Azzurra Bernardini; Massimo Basile; Marco Di Maurizo; Anna Perrone; Sara Renzo; Viola Filistrucchi; Rolando Cimaz; Paolo Lionetti (BMC, 2020)
Abstract Background Arthritis is often an underestimated extraintestinal manifestation in pediatric inflammatory bowel disease (IBD), including sacroiliitis, whose early signs are well detectable at magnetic resonance imaging (MRI). Magnetic resonance enterography (MRE) is an accurate imaging modality for pediatric IBD assessment. We studied the possibility to detect signs of sacroiliac inflammation in a group of children with IBD who underwent MRE for gastrointestinal disease evaluation. Methods We retrospectively reviewed MRE scans performed in pediatric patients with IBD. We looked for signs of sacroiliitis taking the ASAS (Assessment of SpondyloArthritis international Society) criteria as a model. Presence of bone marrow edema (using T2W sequences with fat suppression), diffusion restriction in Diffusion Weighted Imaging (DWI) or Diffusion Weighted Imaging with Background Suppression (DWIBS), and dynamic contrast enhancement were evaluated. Each SI joint was divided into 4 quadrants: upper iliac, lower iliac, upper sacral, and lower sacral. Two blinded observers with experience in pediatric and skeletal imaging independently evaluated the images. Cases upon which there was a disagreement were evaluated by the two reviewing radiologists and a third radiologist with similar experience together. Results We enrolled 34 patients (24 males and 10 females, with mean age at scanning 14.3 years, median 15.3 years; 2 affected by ulcerative colitis, 32 by Crohn's disease) for a total of 59 examinations performed at the time of their first diagnosis or at symptom exacerbations. No patient complained of musculoskeletal symptoms, neither had pathological findings at articular examination. At the time of MRE 25 patients were under treatment for their IBD. Five patients had radiological signs of SI inflammation at MRE, albeit of mild degree. All patients with SI joint edema also had a restricted diffusion in DWIBS or DWI and almost everyone had contrast media uptake. Conclusions Sacroiliitis is one of the extraintestinal manifestation associated with IBD; it is often asymptomatic and clinically underdetected, with an unrelated progression with respect to the underlying IBD. MRE offers the possibility to study SI joints in young patients with IBD who undergo MRE for the investigation of their intestinal condition. Furthermore, we observed that gadolinium enhancement does not improve diagnostic specificity in sacroiliiitis detection.